1976
DOI: 10.1111/j.1476-5381.1976.tb06957.x
|View full text |Cite
|
Sign up to set email alerts
|

TOLERANCE TO THE CARDIOVASCULAR EFFECTS OF Δ9‐TETRAHYDROCANNABINOL IN THE RAT

Abstract: 1Daily intraperitoneal injections of A9-tetrahydrocannabinol (A9-THC, 10 mg/kg) resulted in tolerance to the effects of the cannabinoid on body weight and body temperature within 1-2 weeks of treatment.2 Tolerance failed to develop to the suppression of spontaneous motor activity produced by A9-THC during 28 days of treatment with the cannabinoid (10 mg/kg, i.p. per day). 3 Following treatment with vehicle for 28 days, intravenous administration of A9-THC in anaesthetized rats produced a transient pressor resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

1977
1977
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 13 publications
1
23
0
2
Order By: Relevance
“…However, initial enthusiasm was tempered by the inability to separate the neurobehavioral and cardiovascular effects of cannabinergic ligands and also by a report of the development of rapid tolerance to the hypotensive and bradycardic effects of THC (Adams et al, 1976). Even though a subsequent study in spontaneously hypertensive rats (SHR) found no evidence for tolerance to the same effects during a 10-day treatment period (Kosersky, 1978), interest in this issue waned over the next 20 years.…”
Section: Role Of the Endocannabinergic System In Blood Pressure Regulmentioning
confidence: 99%
“…However, initial enthusiasm was tempered by the inability to separate the neurobehavioral and cardiovascular effects of cannabinergic ligands and also by a report of the development of rapid tolerance to the hypotensive and bradycardic effects of THC (Adams et al, 1976). Even though a subsequent study in spontaneously hypertensive rats (SHR) found no evidence for tolerance to the same effects during a 10-day treatment period (Kosersky, 1978), interest in this issue waned over the next 20 years.…”
Section: Role Of the Endocannabinergic System In Blood Pressure Regulmentioning
confidence: 99%
“…Unfortunately, the initial high anticipation was tempered by a report of the development of rapid tolerance to the hypotensive and bradycardic effects of THC (Adams et al, 1976) and by the failure to separate the cardiovascular and neurobehavioral effects of cannabinoids. Albeit a later study in spontaneously hypertensive rats (SHR) demonstrated no tolerance to the same effects during a 10-day treatment period (Kosersky, 1978), interest in this issue had vanished for the next two decades.…”
Section: Cardiovascular and Respiratory Disordersmentioning
confidence: 99%
“…Although an early study in normotensive rats indicated rapidly developing tolerance to the hypotensive and bradycardic effects of THC (Adams et al 1976), a subsequent study in spontaneously hypertensive rats (SHR) found no evidence for tolerance for the same effects during a similar, 10-day treatment period (Kosersky 1978).…”
Section: Role Of Endocannabinergic System In Hypertensionmentioning
confidence: 99%